CORPORATE REPUTATION, THE & THE BOTTOM LINE - Roger Harwood (Kogan Page, 2005)

(untitled)
Why bother about the corporate reputation? If the price and quality of the products are right who cares about anything else? Once, in the midst of a contract I was undertaking for the food industry, a director of Sainsbury’s (long since moved on) said to me that all the customers care about is price, quality and convenience. But as we discussed the approach of the study, he kept raising, seemingly unconsciously, issues that were not directly about price, quality and convenience yet affected sales – animal rights, Third World labour conditions, e-numbers, salt content, food-miles (the distance foods had travelled to the store), employment conditions, genetically modified foods, directors’ pay and several others. I asked him if he felt people cared about the values of companies they deal with, and whether it mattered that customers trusted the managers. He felt trust was essential. Surely, I suggested, trust is an essential element in any relationship, and most companies need to build relationships to succeed. And if customers (and any other stakeholder group) trusted the managers, surely they were making decisions based on their perceptions of the reputation of the organization?